2016
DOI: 10.1039/c6gc01562j
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of chromium wastes from the tanning industry to produce ceramic nanopigments

Abstract: Growth in the use of colored ceramics and the demand for better quality have stimulated research into the development of new classes of pigments with superior durability and color reproducibility, which can be produced using inexpensive, straightforward, and eco-friendly synthesis procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…2 Chromium is easily converted to a serious pollutant and is harmful to the environment during widespread use. 3,4 Cr(III) ions usually exist in effluents from many industries and excessive emissions can also pollute the environment, although the toxicity of Cr(III) ions is much lower. On the other hand, Cr(III) can transform to Cr(VI), resulting from the effects of pH, oxidizing agent (O 2 ) and so on.…”
Section: Introductionmentioning
confidence: 99%
“…2 Chromium is easily converted to a serious pollutant and is harmful to the environment during widespread use. 3,4 Cr(III) ions usually exist in effluents from many industries and excessive emissions can also pollute the environment, although the toxicity of Cr(III) ions is much lower. On the other hand, Cr(III) can transform to Cr(VI), resulting from the effects of pH, oxidizing agent (O 2 ) and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The composition (wt %) of biochar ash from the XRF analysis is as follows: SiO 2 [41]. Calcium is associated with the lime used in the liming and unhairing steps.…”
Section: Resultsmentioning
confidence: 99%
“…Of every 1000 kg of raw hide, nearly 850 kg is generated as solid wastes in leather processing [1]. Globally, around 90 % of this waste is discharged without any prior treatment due to the high cost of landfill disposal which can harm the environment [2][3][4][5]. In Brazil, in 2005, about 195 000 t of solid waste were generated by the tanning industry, from which 30-40 % stems from leather shavings [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several conditions of the preparation of Cr-Al 2 O 3 were detailed evaluated, and the results showed that the solid tannery waste was more suitable for the usage of ceramic pigments compared to liquid waste. Moreover, the leaching tests indicated that no significant concentration of chromium (below 0.002 μg L − 1 ) were detected [99].…”
Section: Indirect Resource Utilizationmentioning
confidence: 95%
“…Chromium of chrome-containing solid wastes can be recovered by thermal treatment [91], alkaline hydrolysis [92], biochemical method [93,94] and oxidation method [95], subsequently applied in the preparation of pigments or recycled into leather making process as tanning/ retanning agents [96][97][98]. For instance, Da Costa Cunha et al [99] used natural organic matter (NOM)rich water as a gelification agent for the manufacture of ceramic nanopigments, which consisted of α-alumina doped with recycled chromium ions from liquid and solid tannery wastes. The as-prepared Cr-Al 2 O 3 was also used as catalysts for the reduction of 4-nitrophenol.…”
Section: Indirect Resource Utilizationmentioning
confidence: 99%